Chemical Characteristics and Activity of ACE Inhibitors on Fractionation of Tempeh Koro kratok (Phaseolus lunatus) Peptides - Marta Tika Handayani; Retno Indrati; Muhammad Nur Cahyanto (Indonesian Association of Food Technologists, 2019)
Tempeh is a fermented food that is good for health and has high nutritional value. Koro kratok tempeh is one of tempeh which is made from non-soybean legumes. The fermentation process will convert macromolecular compounds to micromolecules thereby increasing bioavailability and providing functional properties. This study aimed to find out the chemical properties of koro kratok tempeh and the effect of peptide molecular weight of koro kratok tempeh on ACE inhibition activity. The results show that koro kratok seeds contained 20.66% protein which total hydrophobic amino acid was 3.32% (w/w protein). This hydrophobic amino acid was higher than that soybean, indicated that koro kratok (Phaseolus lunatus) has a potential producing ACE peptide inhibitors. The koro kratok seeds had ACE inhibitory activity 19.72%. This activity increased to 84.97% when the seeds were fermented for 48h to become tempeh. Peptide fractionation showed that the smaller the molecular weight of the peptide, the higher the ACE inhibitory activity.